A new view of society . or, Essays on the formation of the human character, preparatory to the development of a plan for gradually ameliorating the condition of mankind.; (Longman, Hurst, Rees, Orme, and Brown etc., 1816)
Facsimile reprint: Clifton, Kelley, 1972. With an introd. by J. Saville. XVII p.